Restaurant-style dining in skilled nursing facilities: resident and employee satisfaction - Leson, Suzanne M. (Kansas State University, 2009)
The culture-change movement in skilled nursing facilities is challenging foodservices to consider their role in supporting the paradigm shift to person-centered care. Optimal nutrition for residents supports physical and emotional health of institutionalized older adults. The purpose of this study was to explore factors associated with resident dining in skilled nursing facilities that have transitioned from a traditional foodservice system to restaurant-style dining. The study investigated foodservice employee perceptions of resident satisfaction with foodservices, foodservice employee job satisfaction, and effect of the delivery system transition on employee intent to leave. The study was conducted in two phases. Phase I was a case study of one skilled nursing facility’s transition from the traditional foodservice to restaurant-style dining. Phase II consisted of a survey of residents and employees in seven skilled nursing facilities utilizing restaurant-style dining. Two questionnaires, addressing the constructs of food quality, service quality, and customization relating to resident satisfaction with foodservices, were developed and administered to residents and foodservice employees. The Phase 1 case study revealed differences in financial and unintended weight loss data from pre- to post-menu transitioning. Focus groups provided insight into resident satisfaction with food and foodservices. In both phases, residents were satisfied with restaurant-style dining. Statements regarding the ability to choose foods at meals times scored highly. Service statements such as “Being treated respectfully by employees” were rated high by the residents. Portion sizes and food quality consistency were rated lower by residents. Employee perceptions of resident satisfaction were consistent with the resident ratings of satisfaction. Foodservice employee job satisfaction was high and intent to leave was low. Job satisfaction mediated the relationship between the employee perception of resident service and their intent to leave. Overall, restaurant-style dining appears to be a positive alternative to the traditional foodservice system in skilled nursing facilities. Implications and future research are discussed.
Keywords: nursing home; resident satisfaction; foodservice; restaurant-style dining; employee job satisfaction; culture-change; Gerontology (0351); Health Sciences, Health Care Management (0769); Health Sciences, Nutrition (0570)